Media Pembelajaran Virtual Reality Mata Kuliah Pengantar Teknologi Komputer Pada Jurusan Teknik Komputer Politeknik Negeri Sriwijaya - slamet widodo; Ali Firdaus; M. Miftakul Amin; Azmirianda Muhammad Nurhasyiri; Muhammad Aulia Farhan (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
Learning media is one of the important components for the success of learning in the world of education. Virtual reality as a learning medium allows users to be actively involved in their virtual environment and can do things that are impossible in the real world. The purpose of research with virtual reality technology is to make teaching and learning activities more interesting and flexible. The success of this virtual reality-based learning media is through 2 aspects, namely the attractiveness aspect which is assessed by experts in the multimedia field, and the information and display quality aspect which is assessed by the students of the Computer Engineering Department of the Sriwijaya State Polytechnic. The research method for multimedia development is Luther and Likert scale to calculate the questionnaire given during the socialization of learning media. Respondents in this study amounted to 3 experts and 100 students, which were obtained from the distribution of online questionnaires The test results show that the percentage index of the success rate obtained by this learning media application is 64.9% and is in the "Good" category. The results of data analysis and testing from respondent B, , the test results show that the success rate percentage index is 79.7% and is in the "Good" category. So this learning media is considered to have provided information that can be understood by students and lecturers. Keywords: Learning Media, Virtual Reality, History of Computer Development